Psychosocial factors and subsequent risk of hospitalizations with peripheral artery disease: The Atherosclerosis Risk in Communities (ARIC) Study. (July 2021) - Honda, Yasuyuki; Mok, Yejin; Mathews, Lena; Hof, Jeremy R. Van't; Daumit, Gail; Kucharska-Newton, Anna; Selvin, Elizabeth; Mosley, Thomas; Coresh, Josef; Matsushita, Kunihiro
Abstract: Background and aims: Psychosocial factors are associated with increased risk of cardiovascular disease (CVD). However, associations with peripheral artery disease (PAD) remain uncharacterized. We aimed to compare associations of psychosocial factors with the risk of PAD and two other major atherosclerotic CVD: coronary heart disease (CHD) and ischemic stroke, in the Atherosclerosis Risk in Communities (ARIC) Study. Methods: In 11, 104 participants (mean age 56.7 [SD 5.7] years) without a clinical history of PAD and CHD/stroke at baseline (1990–1992), we evaluated four psychosocial domains: depressive/fatigue symptoms by the Maastricht Questionnaire, social support by the Interpersonal Evaluation List, social networks by the Lubben Scale, and trait anger by the Spielberger Scale. PAD was defined as hospitalizations with diagnosis or related procedures. CHD included adjudicated coronary heart disease and stroke included ischemic stroke. Results: We observed 397 PAD and 1940 CHD/stroke events during a median follow-up of 23.1 years. Higher depressive/fatigue symptoms and less social support were significantly associated with incident PAD (adjusted hazard ratios for top vs. bottom quartile 1.65 [95%CI, 1.25–2.19] and 1.40 [1.05–1.87], respectively). When these factors were simultaneously modeled, only depressive/fatigue symptoms remained significant. Incident CHD/stroke was not associated with either of depressive/fatigue symptoms or social support. Social networks and trait anger were not independently associated with PAD or CHD/stroke. Conclusions: Depressive/fatigue symptoms and social support (especially the former) were independently associated with the risk of hospitalizations with PAD but not CHD/stroke in the general population. Our results support the importance of depressive/fatigue symptoms in vascular health and suggest the need of including PAD when studying the impact of psychosocial factors on CVD. Graphical abstract: Image 1 Highlights: Depressive/fatigue symptoms showed a robust association with incident peripheral artery disease (PAD). Weaker than depressive symptoms, but social support was also associated with PAD. Psychosocial factors were more strongly associated with PAD than ASCVD. The inclusion of PAD is important when studying psychosocial factors on cardiovascular disease (CVD).